SOCIOTAGGING: PARTICIPATORY DESIGN AS FLOOD DISASTER MITIGATION CAMPAIGN IN BOJONGSOANG DISTRICT DURING THE COVID-19 PANDEMIC - Rahmatsyam Lakoro, Agus Sachari, Agung Eko Budiwaspada, Setiawan Sabana (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This article discusses about disaster education for protagonist community in Bojongsoang District, Province of West Java. The district is prone with a high number of hydrometeorological disasters; Disaster Risk Reduction (DRR) campaign conduct to raise awareness about these potential disasters is required, in the period of the covid-19 pandemic. The design was develop by utilizing Sundanese idioms, and then developed into a specific-site design idea for the current generation. Participatory action research method conducted to promote educational media that are close to the daily life of the flood-prone community. Community was involved in design stage to produce disaster literacy. Educational tools design concept developed to deliver the contents through the educational tools, to build knowledge and to educate the community about disaster. The common media using physical platform like information graphic creates the possibility to use virtual content for specific devices. The development of idioms that related to the culture of audience will help the acceptance of information, and use the community as the information agent as well. The communication reaches the affective level; that would enable to build the culture and habitual attitude to deal with disaster or emergency situation.